Entre la diacronía y la sincronía: la palatalización de obstruyentes dorsales en la lengua nivaĉle (mataguaya) - Gutiérrez, Analía (El Colegio de México, A.C., 2024)
This work analyzes the palatalization of dorsal obstruents in the Nivaĉle (Mataguay- an) language from a diachronic and synchronic perspective. Using first-hand data and secondary sources, the trajectories and processes of the Nivaĉle dorsal obstru- ents of Nivaĉle are studied and contrasted with those found in other languages and varieties of the Mataguayan family. Assuming that sound change is phonetically motivated, not only due to perceptual, but also articulatory factors (Recasens 2020), it is hypothesized that the complete palatalization (Bateman 2007) of the Nivaĉle dorsal obstruents involved an intermediate stage of secondary palatalization *k > c > [tʃ͡] and from *x > ç > ʃ, given the comparative evidence in the other Mataguayan languages and the alternations recorded in the available sources on this language. Likewise, it is shown that in addition to the phonologization of [tʃ] [tʃ’] and [ʃ], pal- atalization also expanded to morphological contexts. There are alternations between morphemes with dorsal and alveopalatal initials that in synchrony are not always motivated by the anteriority of the vowel, but by an adjacent coronal consonant. An overgeneralization of the coronal feature is thus hypothesized.